Financial Ratio Performance Analyst PT. Primatama Delivery Ambassador in Surabaya - Reza Anggara (IJESEMS : International Journal of Engineering Science Educatioon and Management System, 2022)
The purpose of this study was to determine the level of financial performance of PT. Primatama Duta Antaran Surabaya which is reviewed through financial ratios (liquidity ratio, solvency ratio, activity ratio, and profitability ratio) in 2015 – 2019. Financial ratios measured include Current Ratio (CR), Quick Ratio (QR), Debt to Total Assets Ratio (DAR), Debt to Equity Ratio (DER), Total Assets Turn Over (TATO), Fixed Assets Turn Over (FATO), Return on Assets (ROA), and Return On Equity (ROE). This type of research is a qualitative research with quantitative data and the use of data collection techniques in the form of documentation in the form of secondary data, namely the annual report of PT. Primatama Delivery Ambassador Surabaya. The data analysis technique used is financial ratios supported by trend analysis. The results showed that the financial performance of PT. Primatama Duta Antaran Indonesia as measured by financial ratios from 2015-2019, that the highest CR was in 2017 of 173.53% and the lowest was in 2017 of -68.59%, the highest QR was in 2017 of 172.31% and the smallest was in 2016 at -70.18%, the lowest DAR was in 2017 at -11.24% and the highest was in 2016 at 7.86%, the lowest DER was in 2016 at 30.49% and the highest was in 2016 at -32.91 %, the highest TATO was in 2017 at 260%, and the lowest was in 2015 at -42.85%, the highest FATO was in 2017 at 40% and the lowest was in 2016 at -44%, the highest ROA was in 2017 at 1,507.41% and the lowest in 2019 was -6,157.14%, the highest ROE was in 2016 of 1,385.